Downregulated F-Box/LRR-Repeat Protein 7 Facilitates Pancreatic Cancer Metastasis by Regulating Snail1 for Proteasomal Degradation - Tang, Liang; Ji, Meng; Liang, Xing; Chen, Danlei; Liu, Anan; Yang, Guang; Shi, Ligang; Fu, Zhiping; Shao, Chenghao (Frontiers in Genetics, 2021)
Pancreatic cancer (PCa) is one of the most aggressive lethal malignancies, and cancer metastasis is the major cause of PCa-associated death. F-box/LRR-repeat protein 7 (FBXL7) regulates cancer metastasis and the chemosensitivity of human pancreatic cancer. However, the clinical significance and biological role of FBXL7 in PCa have been rarely studied. In this study, we found that the expression of FBXL7 was down-regulated in PCa tissues compared with tumor-adjacent tissues, and the low expression of FBXL7 was positively associated with cancer metastasis. Functionally, overexpression of FBXL7 attenuated PANC1 cell invasion, whereas FBXL7 silencing promoted BxPC-3 cell invasion. Forced expression of FBXL7 upregulated the expression of epithelial markers (e.g., E-cadherin) and repressed the expression of mesenchymal markers (e.g., N-cadherin and Vimentin), indicating that FBXL7 negatively regulated the epithelial-mesenchymal transition (EMT) of PCa cells. Furthermore, we identified that FBXL7 repressed the expression of Snail1, a crucial transcription factor of EMT. Mechanistically, FBXL7 bound to Snail1 and promoted its ubiquitination and proteasomal degradation. In vivo studies demonstrated that FBXL7 inhibition promotes PCa metastasis. Taken together, our findings demonstrate that FBXL7 knockdown could efficiently enhance PCa metastasis by regulating Snail1-dependent EMT.